Numerical Analysis of the Stress–Deformation Behavior of Soil–Geosynthetic Composite (SGC) Masses Under Confining Pressure Conditions - Truc T. T. Phan; Meen-Wah Gui; Thang Pham; Bich T. Luong (Buildings, 2025)
The growing application of soil–geosynthetic composites (SGCs) in geotechnical engineering has highlighted the critical role of reinforcement spacing in enhancing structural performance. This study presents a numerical investigation of the stress–deformation behavior of SGC masses under working stress and failure load conditions, considering both confining and unconfined pressure scenarios. A finite element (FE) model was developed to analyze stress distribution, reinforcement strain profiles at varying depths, and lateral displacement at open facings. Results revealed that vertical stresses in reinforced and unreinforced soil masses were nearly identical, while lateral stresses increased notably in reinforced masses, particularly near reinforcement layers and open facings. Closer reinforcement spacing (0.2 m) effectively reduced lateral displacement and enhanced structural stability compared with wider spacing (0.4 m). In some cases, strengthening reinforcement in the upper portion of the SGC mass proved more effective under failure loads in both confining and unconfined pressure conditions. These findings provide critical insights for optimizing reinforcement spacing in SGC systems, with implications for the design of retaining walls and bridge abutments.